Tawny owl prey remains indicate differences in the dynamics of coastal and inland vole populations in southern Finland. Issue 4 (2nd August 2016) - Solonen, Tapio; Karhunen, Jonna; Kekkonen, Jaana A.; Kolunen, Heikki; Pietiäinen, Hannu
Abstract: Some studies suggest that mild winters decrease overwinter survival of small mammals or coincide with decreased cyclicity in vole numbers, whereas other studies suggest non‐significant or positive relationships between mild winter conditions and vole population dynamics. We expect for the number of voles to be higher in the rich and low‐lying habitats of the coastal areas than in the less fertile areas inland. We assume that this geographical difference in vole abundances is diminished by mild winters especially in low‐lying habitats. We examine these relationships by generalized linear mixed models using prey remains of breeding tawny owls Strix aluco as a proxy for the abundance of voles. The higher number of small voles in the coastal area than in the inland area suggest that vole populations were denser in the coastal area. Vole populations of both areas were affected by winter weather conditions particularly in March, but these relationships differed between areas. The mild ends of winter with frequent fluctuations of the ambient temperature around the freezing point ("frost seesaw") constrained significantly the coastal vole populations, while deep snow cover, in general after hard winters, was followed by significantly lowered number of voles only in the inland populations. Our results suggest that coastal vole populations are more vulnerable to mild winters than inland ones. We also show that tawny owl prey remains can be used in a meaningful way to study vole population dynamics.